Infant formula with 2′-FL + LNnT positively modulates the infant gut microbiome: An in vitro study using human intestinal microbial ecosystem model - Tonon, Karina Merini; Salgaço, Mateus Kawata [UNESP]; Mesa, Victoria; Bento Mosquera, Elaine Martins; Tomé, Thaís Moreno; Freitas, Patrícia Vilar; Machado Alencar, Natália Manzatti; Sartoratto, Adilson; Lazarini, Tamara; Sivieri, Katia [UNESP] (Elsevier, 2023)
We investigated the effect of infant formula (IF) with human milk oligosaccharides [(HMOs); 2′-fucosyllactose (2′FL; 1 g L−1) and lacto-N-neotetraose (LNnT; 0.5 g L−1)] on gut microbiota using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) model with faecal samples from 6 months old infants. Samples of the colonic contents were cultured and analysed by 16S rRNA gene sequencing and microbial metabolites by gas chromatography-mass spectrometry. A key finding was an expressive increase in Lactobacillus, Bifidobacterium, and short-chain fatty acids, primarily acetate, accompanied by a drastic reduction in Clostridium, Veillonella, and Eubacterium. This study showed that an IF with 2′-FL + LNnT positively modulates the infant gut microbiome by increasing beneficial bacteria while reducing potential pathogens.